Applying Constant Comparative Method with Multiple Investigators and Inter-Coder Reliability - Olson, Joel; McAllister, Chad; Grinnell, Lynn; Gehrke Walters, Kimberly; Appunn, Frank (Qualitative report, 2016)
Building on practice, action research, and theory, the purpose of this paper is to present a 10-step method for applying the Constant Comparative Method (CCM) of grounded theory when multiple researchers perform data analysis and meaning making. CCM is a core qualitative analysis approach for grounded theory research. Literature suggests approaches for increasing the credibility of CCM using multiple researchers and inter-coder reliability (ICR), but documentation of methods for collaboration on CCM data analysis is sparse. The context for developing the10-step CCM approach was a qualitative study conducted to understand the impact of webcams on a virtual team. To develop a methodology for the study, the researchers reviewed grounded theory literature to synthesize an approach for conducting CCM with multiple researchers. Applying action research, an integration of literature and practical experience conducting the qualitative study resulted in a model for using CCM with multiple researchers performing data analysis. The method presented in this paper provides practical guidance for applying CCM collaboratively and shares the researchers’ perspectives on the value of ICR.